Discovery of Novel Peptidomimetics for Brain-Derived Neurotrophic Factor using Phage Display Technology: Designing a BDNF-mimicking peptide - Nafian, Fatemeh; Rasaee, Mohammad Javad; Yazdani, Shahin; Soheili, Zahra Soheila (Iranian Journal of Pharmaceutical Sciences, 2018)
Brain-Derived Neurotrophic Factor (BDNF) is a neuroprotectant candidate for neurodegenerative diseases. However, there are several clinical concerns about its therapeutic applications. In the current study, we selected BDNF-mimicking small peptides from phage-displayed peptide library as alternative molecules to the clinical challenges. The peptide library was screened against BDNF receptor (Neurotrophic Tyrosine Kinase Receptor Type 2, NTRK2) and evaluated by ELISA. Polyclonal phage ELISA indicated that target populations were enriched round by round and the panning process was truly effective. The results of monoclonal phage-ELISA showed that all clones had principally bound to NTRK2 but fifteen best clones were sequenced, which twelve of them have SGVYKVAYDWQH (peptide 1) sequence, two pairs were GLHTSATNLYLH (peptide 2), and TVLSHPSTATLI (peptide 3) and one sequence was QQRPYVQDLRLI (peptide 4). Alignment of these peptides and BDNF sequence showed that the resulting peptides conformationally mimicked loop 2 (E40-KVPVSKGQLK-Q51) of BDNF. This region of BDNF is responsible for specific receptor binding and biological activity. According to the similarity of these peptides with BDNF, they could be considered as novel peptidomimetics with therapeutic properties. In addition, modeled peptides were submitted to Protein Model Data Base (peptides 1, 2, 3 and 4 as PMDB ID: PM0081104, PM0081105, PM0081106, PM0081107, respectively).